The relationship between swimming time and rhythmic ability - Zachopoulou, E.; Mantis, K.; Dwerri, V.; Mavidis, A. (2001)
Coordination is the procedure of using the appropriate muscles at the right moment, under a certain percentage of intention, within a structured sequence of movement patterns. Rhythmic ability is an important factor of all the coordinating movements and has two parameters: rhythmic accuracy and rhythm maintenance. The purpose of the present study was to examine the relationship between the two parameters of rhythmic ability and swimming performance in free style and backstroke. It was hypothesized that the scores of the rhythm tests would correlate highly with swimming performance. The sample of the research consisted of 76 children (40 boys and 36 girls), aged 8 - 10 years old, who had experience in swimming training for 1.5 to 2 years. All children underwent a test for the evaluation of rhythm parameters, in two rhythm tempos, and swimming performance was evaluated by the time they scored for swimming 50 meters. Pearson`s coefficient of determination revealed no correlation between time in two styles and rhythmic accuracy scores. Swimming time correlated significantly to the maintenance scores in both tempos (slow tempo ® r = 0.78, p = 0.00, fast tempo ® r = 0.59, p = 0.00). The results showed that swimming training significantly improved rhythm maintenance. It was concluded from the above that the maintenance of rhythm, perhaps, plays a significant role for swimming performance. On the other hand, rhythmic accuracy hasn`t affected performance in swimming, due to absence of any external rhythmic stimuli, during swimming training, to which the trainee have to synchronize their movements.